2016 IEEE 23rd International Conference on Software Analysis, Evolution, and Reengineering (SANER) 2016
DOI: 10.1109/saner.2016.115
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Decision Criteria of Software Developers Based on Prospect Theory

Abstract: To enhance the quality of software, many software development support tools and software development methodologies have been proposed. However, not all proposed tools and methodologies are widely used in software development. We assume that the evaluation of tools and methodologies by developers is different from the evaluation by researchers, and that this is one of the reasons why the tools and methodologies are not widely used. We analyzed the decision criteria of software developers as applied to the tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Bell e et al (2018) identified how prospect theory explains cognitive biases in public policy and decision-making. Prospect theory is also applied to learn decisionmaking in software development choices (Kina et al, 2016;Peng and Yang, 2017). It has been extensively applied in political decision-making literature (Boettcher, 2004;Mercer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Bell e et al (2018) identified how prospect theory explains cognitive biases in public policy and decision-making. Prospect theory is also applied to learn decisionmaking in software development choices (Kina et al, 2016;Peng and Yang, 2017). It has been extensively applied in political decision-making literature (Boettcher, 2004;Mercer, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Risk aversion has wider generalisability towards, for example, general decision making under risk (Abdellaoui et al, 2007). Kina et al (2016) examined software engineer tool adoption practices and found they did not always maximise profit by adopting new tools, instead relying upon the known certainty of familiar tools. This suggests a certainty effect or bias in play.…”
Section: Cognitive Processing Stylesmentioning
confidence: 99%
“…Risk aversion has wider generalizability toward, for example, general decision making under risk (Abdellaoui et al, 2007). Kina et al (2016) examined software engineer tool adoption practices and found that when new tools are not guaranteed to maximize profit and contain risks, engineers are more risk averse and instead rely upon the known familiarity of familiar tools. This suggests a certainty effect, or bias in play.…”
Section: Risk Aversionmentioning
confidence: 99%